MENINGKATKAN KEMAMPUAN MENYIMAK ANAK USIA 5-6 TAHUN MELALUI BERMAIN PESAN BERANTAI DI KELOMPOK BERMAIN TALITAKUM FUN KIDS KECAMATAN SIAK HULU KABUPATEN KAMPAR - Desly Manalu; Tri Utami; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study are as follows: 1) To determine which method chain messages can improve listening skills of children aged 5-6 years in Talitakum Fun Kids Playgroup Siak Hulu District of Kampar regency. 2) To find out how the teachers in improving listening skills of children aged 5-6 years through the method of chain messages in Talitakum Fun Kids Playgroup Siak Hulu District of Kampar regency. 3) To know how much the increase listening skills of children aged 5-6 years through the method of chain messages in Talitakum Fun Kids Playgroup Siak Hulu District of Kampar regency. The subjects were children Talitakum Fun Kids Playgroup Siak Hulu District of Kampar regency with the number of children as many as 18 children consisting of 8 men and 10 daughters. Collecting data using observation and documentation. Data analysis techniques used in this research is descriptive analysis techniques. The results show a big increase listening skills in children aged 5-6 years with the adoption of chain messages play in Fun Kids Play Group Talitakum Siak Hulu District of Kampar regency of action prior to the first cycle to an increase of 44.4%. While improving listening skills from the first cycle to the second cycle of 23:04%, and the overall improvement of listening skills by 77.77%Keywords: Listening skills, play of messages chain